When and How Should we be Measuring Adherence to Antiretroviral Therapy in Resource-Limited Settings? - Denise Evans; Matthew P Fox (Journal of Clinical Research In HIV AIDS And Prevention, 2013)
This perspective reviews practical approaches to measuring ART adherence in resource‑limited settings. It weighs self‑report, pill counts, pharmacy refill data, and biologic measures, emphasizing feasibility, bias, and programmatic integration to support sustainable HIV care.